Uchronia designing time - Schmid, Helga (Birkhäuser, 2020)
The transformation of society from an agrarian to an industrial, and finally an urbanized way of living and working has created a fundamental change in our understanding of time: more and more this is determined by a 24/7 mentality, which is demanded for 24 hours on 7 days of the week. The move from natural time – via the mechanical clock – to the digital age leads to a fragmentation of time that deeply affects our daily biological and social rhythm. Focusing on objects in our designed environment, this book investigates potential risks such as that arising from a new perception of time – by exploring the concept of uchronia, a term derived from the Greek u-topos and meaning "no time" or "non-time"
Keywords: bicssc / Residential buildings, domestic buildings; bicssc / Building construction & materials; bisacsh / ARC024000 ARCHITECTURE / Buildings / General; bisacsh / DES000000 DESIGN / General; bisacsh / DES011000 DESIGN / Product; Design; Zeit; Soziologie; Chronobiologie; Hardcover, Softcover / Kunst/Architektur